So alike and yet so different: A comparison of the Uruguay Round and the Doha Round - Peter Kleen (European Centre for International Political Economy (ECIPE), 2008)
As the first multilateral trade round to be conducted under the auspices of the WTO, the Doha Round is beginning to appear as protracted, complicated and politically controversial as the last round under the GATT - the Uruguay Round. In this essay Peter Kleen finds that the differences between the two rounds are equally striking. He undertakes a substantive comparison of the Uruguay Round and the Doha Round, drawing insights and lessons for any future efforts to liberalise trade within the WTO. Covering the initiation and evolution of each round, including the major players within each, he concludes that negotiating trade agreements must remain the raison d'etre of the WTO, no matter how complicated it has become. Such negotiations, however, could take a less ambitious and more incremental form than these big rounds and must be able to muster support from the global business community if trade liberalisation is to continue advancing.
Keywords: 330